1999
DOI: 10.1006/viro.1998.9588
|View full text |Cite
|
Sign up to set email alerts
|

Sμbp-2 Represses the Epstein–Barr Virus Lytic Switch Promoter

Abstract: Smubp-2 is a novel transcription factor that was first identified through its interaction with the immunoglobulin Smu region (Mizuta et al., 1993) and has been cloned by virtue of its binding to two 12-O-tetradecanoylphorbol-13-acetate-responsive elements in the Epstein-Barr virus immediate-early BZLF1 promoter (Gulley et al., 1997). In this report, we examined the effect of Smubp-2 overexpression on BZLF1 prom oter activity. Overexpression of Smubp-2 in the B lymphocyte cell line BJAB caused repression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Negative regulatory elements of the BZLF1 promoter lie both within (36,43,60) and outside (42,43,49) the Ϫ221 to ϩ 20 region. We showed here that ZVR does not bind any of the known proximal negative elements (Fig.…”
Section: Vol 75 2001mentioning
confidence: 99%
See 1 more Smart Citation
“…Negative regulatory elements of the BZLF1 promoter lie both within (36,43,60) and outside (42,43,49) the Ϫ221 to ϩ 20 region. We showed here that ZVR does not bind any of the known proximal negative elements (Fig.…”
Section: Vol 75 2001mentioning
confidence: 99%
“…Unfortunately, the authors failed to detect a specific protein complex that recognized this sequence. Recently, Zhang et al (60) showed that the ubiquitous factor Sbp-2 represses transcription of the BZLF1 promoter, with this repression being significantly affected by an element located between nt Ϫ93 and Ϫ79. Whether this or the ZIIR element is an Sbp-2 DNAbinding site remains unclear.…”
mentioning
confidence: 99%
“…Besides JDP2, several factors have been reported to suppress the BZLF1 promoter. SMUBP-2, a transcription factor first identified through its interaction with the immunoglobulin Smu region, represses Zp activation by TPA (37). ZEB proteins restrict BZLF1 expression by binding to the ZV element of the promoter (38 -40).…”
Section: Discussionmentioning
confidence: 99%
“…IGHMBP2 is ubiquitously expressed and consists of 15 exons encoding a protein of 993 amino acids that possesses a putative DNA helicase region, an R3H motif, and a zinc-finger AN1-like domain. Although the physiological function of IGHMBP2 is not known in detail, the protein is suspected to be involved in immunoglobulin-class switching, pre-mRNA processing, and regulation of transcription through DNA-binding or interaction with TATA-binding proteins (Fukita et al 1993;Molnar et al 1997;Zhang et al 1999;Miao et al 2000;Liepinsh 2003). Fukita et al (1993) first showed that IGHMBP2 binds to singlestranded DNA with 5¢-phosphorylated guanine-rich sequences related to the immunoglobulin l-chain switch (Sm) region.…”
Section: Discussionmentioning
confidence: 99%